(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The search for novel antibiotics for treating human-wildlife infections has not stopped. This study isolated and characterized bacteria and fungi from wildlife geophagic termite mounds (TMs) using standard microbiological procedure. Four composite samples of TMs evident to be eaten by wildlife were randomly collected (TM1, TM2, TM3 and TM4) in addition with a composite forest soil (FS5) that showed no sign of consumption. With the use of appropriate media, all samples were subjected to microbiological analysis covering morphological, biochemical (for bacteria), colonial and cellular morphology (for fungi). Bacteria and fungi cells isolated and characterized from respective soil samples include; Streptomyces lydicus/Aspegillus niger (TM1), Paenibacillus polymyxa/Penicillium digitatum (TM2), Pseudomonas fluorescens/Fusarium spp. (TM3), Bacillus subtilis/Aspergillus flavus (TM4) and Acinetobacter radioresistens/Geotricihum candidum (FS5), all of which have both beneficial and harmful characteristics. Wildlife may be affected by pathogenic organisms when consuming TMs for medicinal reasons. Dhaka Univ. J. Pharm. Sci. 21(1): 53-58, 2022 (June)